Lung Pharmacokinetics of Tobramycin by Intravenous and Nebulized Dosing in a Mechanically Ventilated Healthy Ovine Model. (August 2019) - Dhanani, Jayesh A.; Diab, Sara; Chaudhary, Jivesh; Cohen, Jeremy; Parker, Suzanne L.; Wallis, Steven C.; Boidin, Clément; Barnett, Adrian; Chew, Michelle; Roberts, Jason A.; Fraser, John F.
Editor's Perspective: What We Already Know about This Topic: For most bacterial pneumonia, the lung interstitium is considered to be the site of infection, and adequate antibiotic concentrations are important for drug effect Despite systemic antibiotic therapy, therapeutic failure is common, perhaps due to poor lung penetration, and resulting low interstitial space fluid antibiotic concentrations Increasing systemic antibiotic doses in order to increase interstitial space fluid antibiotic concentrations could lead to toxicities such as nephrotoxicity What This Article Tells Us That Is New: In a mechanically ventilated healthy large animal model, nebulized tobramycin produced higher peak lung interstitial space fluid concentrations, as well as higher initial epithelial lining fluid concentrations, with lower plasma concentrations than were observed after intravenous administration due to more extensive lung penetration Background: Nebulized antibiotics may be used to treat ventilator-associated pneumonia. In previous pharmacokinetic studies, lung interstitial space fluid concentrations have never been reported. The aim of the study was to compare intravenous and nebulized tobramycin concentrations in the lung interstitial space fluid, epithelial lining fluid, and plasma in mechanically ventilated sheep with healthy lungs. Methods: Ten anesthetized and mechanically ventilated healthy ewes underwent surgical insertion of microdialysis catheters in upper and lower lobes of both lungs and the jugular vein. Five ewes were given intravenous tobramycin 400 mg, and five were given nebulized tobramycin 400 mg. Microdialysis samples were collected every 20 min for 8 h. Bronchoalveolar lavage was performed at 1 and 6 h. Results: The peak lung interstitial space fluid concentrations were lower with intravenous tobramycin 20.2 mg/l (interquartile range, 12 mg/l, 26.2 mg/l) versus the nebulized route 48.3 mg/l (interquartile range, 8.7 mg/l, 513 mg/l), P = 0.002. For nebulized tobramycin, the median epithelial lining fluid concentrations were higher than the interstitial space fluid concentrations at 1 h (1, 637; interquartile range, 650, 1, 781, vs. 16 mg/l, interquartile range, 7, 86, P < 0.001) and 6 h (48, interquartile range, 17, 93, vs. 4 mg/l, interquartile range, 2, 9, P < 0.001). For intravenous tobramycin, the median epithelial lining fluid concentrations were lower than the interstitial space fluid concentrations at 1 h (0.19, interquartile range, 0.11, 0.31, vs. 18.5 mg/l, interquartile range, 9.8, 23.4, P < 0.001) and 6 h (0.34, interquartile range, 0.2, 0.48, vs. 3.2 mg/l, interquartile range, 0.9, 4.4, P < 0.001). Conclusions: Compared with intravenous tobramycin, nebulized tobramycin achieved higher lung interstitial fluid and epithelial lining fluid concentrations without increasing systemic concentrations. Abstract : In a mechanically ventilated healthy large animal model, nebulized tobramycin produced higher peak lung interstitial space fluid concentrations, as well as higher initial epithelial lining fluid concentrations, with lower plasma concentrations than were observed after intravenous administration due to more extensive lung penetration.Supplemental Digital Content is available in the text.